A study of contrast sensitivity and quality of life following phacoemulsification with two different types of aspheric lenses - Rohana, Abdul Rashid (2008)
Aspheric lens has emerged as a new landscape of intraocular design in order to provide a better quality of vision. Measurement of contrast sensitivity and vision related quality of life would assess the optical and visual performance of these aspheric lenses. To compare the visual acuity, contrast sensitivity and vision related quality of life following phacoemulsification and implantation of two aspheric lenses among age related senile cataract patients attending ophthalmology clinic in Hospital Universiti Sains Malaysia, Kubang Kerian and Hospital Raja Perempuan Zainab II (HRPZ II), Kota Bharu, Kelantan. A total of 112 eyes of 112 patients were randomized to receive either Akreos Adapt Advanced Optic (n=61) or Tecnis Z9003 (n=51). Patients were selected according to the inclusion and exclusion criteria. At 3 months postoperative period, patients were assessed for contrast sensitivity under photopic and mesopic using CSV1 000 and modified VF -14 questionnaires was used to assess the vision related quality of life. Comparison of means of each parameter was made between the intraocular lenses. Data was analyzed by either Chi-square or independent t test with p value less than 0.05 was considered significant. The vision related quality of life using the VF -14 scores were further divided into near vision, intermediate vision and distant vision items. The mean visual acuity and contrast sensitivity in photopic and mesopic lightning at 3, 6, 12 and 18 cpd showed very similar results in Akreos Adapt AO and Tecnis Z9003. There was no significant difference between the two intraocular lenses. The VF-14 scores in Akreos Adapt AO has a mean of 98.57 (2.51) whereas the Tecnis Z9003 has a mean of 97.18 (5.46). The total quality of life scores also revealed no significant difference. Postoperative visual acuity and contrast sensitivity in both intraocular lenses were almost comparable. Neither Akreos Adapt AO nor Tecnis Z9003 showed a significant difference in contrast sensitivity and vision related quality of life at 3 months postoperative period.